Prediksi Pembukaan Peluang Usaha Di Kecamatan Medan Amplas Menggunakan Algorima Naive Bayes - Yulia Fatmi (RJOCS (Riau Journal of Computer Science), 2019)
Naive Bayes algorithm can be used to predict a situation, in this study discussed how the Naive Bayes algorithm predicts a business opportunity in an environment. Environmental needs factor is a benchmark for the feasibility of opening a business, there are two types of businesses offered, namely trade and services, from a survey conducted on 50 consumer samples, consisting of 27 women and 23 men with certain criteria. From the data obtained the analysis will be based on the quantification of trade-offs using certain probability values. The selection of Naive Bayes Algorithm in this analysis is because this algorithm only requires a small amount of training data to determine the estimation of parameters needed in the classification process. From the results of this study, it is expected to be able to determine the prediction of business opportunities for the people of Medan Amplas.